Penerapan Qawaid Fiqhiyyah dalam Menyikapi Fenomena Gaya Hidup Muslim Milenial - Noviana, Elly; Norhadijah; Eva Susanti (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2025)
This study examines the understanding and application of Qawaid Fiqhiyyah among millennial Muslims in facing modern life challenges. The study identifies that while many millennial Muslims have basic knowledge of Qawaid Fiqhiyyah, they struggle to apply it in daily life. The main factors influencing this include a lack of formal education on fiqh, the impact of globalization and technology, and social pressures that promote a modern lifestyle often misaligned with Islamic principles. The primary challenges in applying Qawaid Fiqhiyyah in the digital era include limited indepth understanding, the influence of popular culture, and the dynamics of the digital economy, which are not yet fully aligned with Islamic law. However, Qawaid Fiqhiyyah remains relevant as a guideline for various aspects of millennial Muslim life, particularly in finance, consumption, social interactions, and technology usage. To address these challenges, increasing fiqh literacy through more inclusive education, utilizing digital media as a platform for Islamic teachings, and adopting a practical approach to explaining Islamic legal principles are essential. With a better understanding, millennial Muslims can lead a more balanced life, uphold Islamic values, and wisely navigate the changes of the modern era.